The Publications of the Bedfordshire Historical Record Society Volume X - Fowler, G. Herbert (Publications Bedfordshire Hist Rec Soc Ser., 1926)
The Publications of the Bedfordshire Historical Record Society, vol. 10 'Digest of the charters preserved in the cartulary of the Priory of Dunstable' by G. Herbert Fowler. This digest is from a thirteenth century manuscript, with additions to the fifteenth century, preserved in the British Library as Harleian MS 1885. It uses a mixture of transcription, translation, abstracting and listing to present the charters and other documents in the cartulary. The editor has prioritised charters and older documents from the twelfth and thirteenth centuries for the most extensive treatment. Dunstable Priory held land in many of the surrounding parishes and this volume is a valuable source for land holding, people and place names in the southern part of Bedfordshire in this period. There are detailed notes, fourteen pedigrees (some extensive), a map of south Bedfordshire and thorough indexes.